IMPROVING PROSOCIAL BEHAVIOR OF CHILDREN OF B TK TUNAS HARAPAN 1 TUNGGUNJAGIR THROUGH TRADITIONAL GAMES - Lina Eka Retnaningsih; Sri Zulfida; Ferri Yonantha (Abata : Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This study is conducted by the low of prosocial behavior of B Class of TK Tunas Harapan. This is shown in the attitude of most children who do not care about the condition of friends, often fighting over toys because they do not want to share with friends, laughing at friends who fall when they need help, teasing other friends inside or outside the classroom. Therefore, this study aims to describe the process and results of the implementation of traditional games to improve the prosocial behavior of children in B class of TK Tunas Harapan. This The method of this study is Action Research using Kemmis and Mc Taggart Classroom Action Research model consisting of four stages, namely planning, action, observation, and reflection. This study was conducted in 2 cycles. Each cycle consisted of 6 meetings. The data was analyzed qualitatively and quantitatively. The results of this study indicate that there is an improvement on children's prosocial behavior through traditional games, as evidenced by the average pre-intervention prosocial behavior score 5,08, then it was improved on Cycle I that was 7,67 and on Cycle II that was 10,83 out of the maximum score 12.